HUBUNGAN PERSEPSI PERAWAT TENTANG GAYA KEPEMIMPINAN KEPALA RUANGAN DENGAN KINERJA PERAWAT DALAM PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUANG RAWAT INAP - Mehara Wati, Ira; Setiawati, Setiawati; Mulyaningsih, Siti (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2026)
Background: The role of head nurse has an important role in determining the quality of nursing services, one of which is the performance of nurses in carrying out nursing documentation. Good documentation is not only an improvement, but is important for the continuity of care, patient safety, and communication between health professionals. Objective: This study aims to determine nurses' perceptions of the head nurse's leadership style with nurse performance in nursing documentation. Method: This study is an analytical survey study with a cross-sectional approach. A sample of 46 respondents who are team leaders and nurses with a total sampling method. Data were collected using questionnaires and observation sheets. Results: Based on the results of the study, 37 respondents (80.4%) stated that the head nurse’ leadership style was democratic and 9 respondents (19.6%) stated that the head nurse’ leadership style was authoritarian. A total of 30 respondents (65.2%) did incomplete dormitory documentation and only 16 respondents (34.8%) did complete documentation. The results of the chi-square test showed a relationship between leadership style and nurse performance in nursing documentation with a p-value = 0.001. Conclusion: There is a relationship between the head nurse’ leadership style and nurses' performance in documenting nursing care in inpatient wards. Head nurses need to implement an appropriate leadership style to improve nurses' performance, particularly in documenting patient care, from assessment to evaluation. This can enhance mutual care and minimize service errors.